Virtual Valcamonica: collaborative exploration of prehistoric petroglyphs and their surrounding environment in multi-user virtual reality - Kulik, Alexander; Kunert, André; Beck, Stephan; Matthes, Carl-Feofan; Schollmeyer, Andre; Kreskowski, Adrian; Fröhlich, Bernd; Cobb, Sue; D'Cruz, Mirabelle (Massachusetts Institute of Technology Press, 2018)
In this paper, we present a novel, multi-user, virtual reality environment for the interactive, collaborative 3D analysis of large 3D scans and the technical advancements that were necessary to build it: a multi-view rendering system for large 3D point clouds, a suitable display infrastructure and a suite of collaborative 3D interaction techniques. The cultural heritage site of Valcamonica in Italy with its large collection of prehistoric rock-art served as an exemplary use case for evaluation. The results show that our output-sensitive level-of-detail rendering system is capable of visualizing a 3D dataset with an aggregate size of more than 14 billion points at interactive frame rates. The system design in this exemplar application results from close exchange with a small group of potential users: archaeologists with expertise in rock-art and allows them to explore the prehistoric art and its spatial context with highly realistic appearance. A set of dedicated interaction techniques was developed to facilitate collaborative visual analysis. A multi-display workspace supports the immediate comparison of geographically distributed artifacts. An expert review of the final demonstrator confirmed the potential for added value in rock-art research and the usability of our collaborative interaction techniques.